2019
DOI: 10.1016/j.jor.2019.02.020
|View full text |Cite
|
Sign up to set email alerts
|

Results of a fast-track knee arthroplasty according to the experience of a multidisciplinary team

Abstract: Introduction: Fast-Track is a multidisciplinary system that has changed the perception of total knee arthroplasty surgery. It's based on the education of the patient, an increased autonomy, adequate pain control and early mobilization. In the bibliography, there are no articles that refer to the evolution of the protocol once established, and most of them are comparatives with the previously existing conventional system. For this reason, the objective of our work is to study the evolution of the clinical resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…21,22 Early mobilization allows for better rehabilitation with a lower risk of falls-an essential goal in fast-track protocols. 23,24 Preliminary studies show higher morphine consumption than that found in our study with periarticular infiltration. Fan et al reported a total consumption of 37.8 mg using LIA.…”
Section: Discussionmentioning
confidence: 43%
See 1 more Smart Citation
“…21,22 Early mobilization allows for better rehabilitation with a lower risk of falls-an essential goal in fast-track protocols. 23,24 Preliminary studies show higher morphine consumption than that found in our study with periarticular infiltration. Fan et al reported a total consumption of 37.8 mg using LIA.…”
Section: Discussionmentioning
confidence: 43%
“…A logistic regression using 50-resampling missing imputation was estimated for intended-to-treat analysis of total morphine consumption, 24…”
Section: Methodsmentioning
confidence: 99%
“…The fast-track program continued to use existing clinical guidelines for state-of-the-art working protocols and continuous improvement [12]. Once a patient was considered eligible for TKA, they were invited to participate in an educational workshop with a relative.…”
Section: Ft Group 2016 Fast-track Programmentioning
confidence: 99%
“…They are characterized by changes to the surgical procedure and the post-discharge function [ 5 , 6 ] and by the participation of different specialists at all stages [ 3 , 7 ]. Their goal is to reduce the physiological and psychological stress of surgery, achieve earlier mobilization and faster recovery, and reduce length of stay (LOS) and hospital costs [ 8 ].…”
Section: Introductionmentioning
confidence: 99%